Appropriateness degree of the Educational Environment to Include the Students with Disabilities at Governmental Schools in Gaza Governorate - Zeedia, Farah (Dirasat: Educational Sciences, 2022)
This study aims at recognizing the appropriateness of educational environment at public primary schools in Gaza to include students with disabilities from educational councilors perspective , for this, the researcher had used the descriptive analytical approach in order to conclude main study results.Moreover, the researcher had chosen 145 councilors as study population at Gaza east and west educational administrations in the educational year 2017-2018. The study main findings concluded that the majority of educational councilors have positive attitudes with regard the inclusive education that embrace students with disabilities at primary schools, where the social domain had scored the first order by (75.13%)., and the academic domain came at last order by (71.06%).On the other hand, the study results pointed to the lack of assistive devices and weak funding for inclusive practices are one of main challenges of inclusive practices, having said that, the study samples set group of recommendations as improving the physical accessibility of schools and provide trainings to teachers in order for more understanding and implementation of inclusive practices.In this regard, it was recommended that focusing on emphasize on a welcoming, social, and violence-free school environment between students, because of their effective effects on students with disability from an increase in their academic achievement.